Science education in early childhood education: A teaching look at the formation of children (Revista Contexto & Educação, 2023)
This work is the result of a research, a case study, carried out in an early childhood school in the municipal network of Uruguaiana/RS. The researched group was composed of 16 teachers. The research aimed to verify the perceptions, knowledge and approaches of teachers about science teaching; investigate how the process of continuing education of these teachers in the municipal education system occurs and diagnose difficulties and facilities of teachers to approach science teaching. The data were obtained through the application of a semi-structured questionnaire and the qualitative assessment was developed according to the content analysis. The results showed that the teachers' perceptions about science teaching are varied and wide. Regarding the pedagogical practices developed, it was found that they are consistent with the stage of development of the children, however there is a lack of activities that instigate the children to formulate hypotheses and experiment with playful activities focusing on the sciences. However, it is pointed out as an alternative for the improvement of didactic-pedagogical practice, the continuous training of teachers and the development of educational strategies contextualized with the other areas of knowledge, in order to make classes more interesting and promote the full development of children.